Implementation of Dual System Education (DSE) Program in Accounting Expertise Program at SMK PGRI 1 Ponorogo - Putri, Novela Nariska; Martono, Trisno; Sudiyanto, Sudiyanto (International Journal of Active Learning, 2019)
The research was carried out at SMK PGRI 1 Ponorogo, Ponorogo Regency, East Java Province. This research aimed to determine the effectiveness of the implementation of the dual system education (DSE) program in the accounting Expertise program at SMK PGRI 1 Ponorogo. There were 9 validators in this research. The results showed that the implementation of the dual education system program in the accounting expertise program at SMK PGRI 1 Ponorogo has not been running effectively as evidenced by the average score of the overall input/planning, process/implementation, and product/assessment of 3.75, while for the effective standard, the scale is 4. The Input/planning stage includes the selection of competencies (4), determination of industry (4.78), preparation of programs (4.78), debriefing of participants (4.78), determination of mentors (4.67). The overall average score is 4.60 ? 4, so it is said to be effective. The process/implementation stage consists of the preparation of the DSE journal (3.78), DSE monitoring (4), and portfolio documentation (2.78). The overall average score is 3.52 ? 4, so it is said to be ineffective. The product/assessment stage includes the supervisor assessment (4.11), industry certification (4.78), and score reporting (3.55) with the overall score of 4.14, which is said to be effective.